An Investigation of a Printer’s Block (Manchester, John Rylands Library, 17252) - Emerson Storm Fillman Richards (Perspectives Médiévales)
Housed in the United Kingdom, at the John Rylands Library in Manchester (item number 17252), the xylographic printing block that we study in this article has an uncertain date. Some scholars believe that it dates to the fifteenth century and that it is, consequently, the oldest extant woodblock printing apparatus. Other scholars believe that it was made in the eighteenth century and it imitates the medieval iconography. Lacking more scientific investigations, the exact date of the woodblock cannot be established. Our article investigates both possibilities of dating in regard to the iconographic tradition (the carved image on the block represents a scene from the life of St. John, largely inspired by the illustrated Apocalypses of the thirteenth and fourteenth centuries) and of our understanding of the block. We examine, therefore, the status of the block as an object that is an authentic fifteenth-century object and as an eighteenth-century imitation.